(Infra)structural Discontinuity: Capital, Labour, and Technological Change. Issue 2 (18th October 2022) - Cole, Matthew
Abstract: The so‐called age of AI, industry 4.0, the fourth industrial revolution, etc. all attempt to conjure into existence a new technological paradigm. Should we believe the hype? This paper draws on neo‐Schumpeterian and régulation theory to widen the scope of this debate and examine techno‐economic and institutional discontinuities. In exploring these discontinuities, this paper argues, first, that growth regimes are not necessarily tenable as indicators of new paradigms, and, second, that there are (infra)structural discontinuities between the ICT/post‐Fordist era and those of the AI/platform era. Platformisation entails a distinct institutional logic, regime of accumulation (RA) and mode of social régulation (MSR). The clusters of technological and institutional changes behind this shift have not yet been sufficiently addressed by economic geography and associated literatures. In reconceptualising the shift in terms of (infra)structural discontinuity, the paper synthesises neo‐Schumpeterian and régulation theory to identify both technological and institutional changes in the régulation of capitalist accumulation.